ModGraph meets Xcore: Combining Rule-Based and Procedural Behavioral Modeling for EMF - Winetzhammer, Sabine; Westfechtel, Bernhard (Electronic Communications of the EASST, 2013)
Model-driven software engineering aims at increasing productivity by developing high-level executable models. The Eclipse Modeling Framework (EMF) significantly contributes toward this goal. Unfortunately, EMF supports only structural models based on the Ecore metamodel. Recently, Xcore has been developed to extend EMF with behavioral modeling. To this end, Xcore provides a single textual language for both structural and behavioral modeling. While Xcore follows a procedural approach to behavioral modeling, ModGraph is an EMF-based tool based on a rule-based paradigm (graph transformation rules, which allow to specify behavior in a declarative way). The combination of EMF, Xcore, and ModGraph results in an environment for model-driven software engineering which provides full-fledged support for both structural and behavioral modeling. Altogether, we obtain an environment in which software engineers are concerned only with models rather than with programs.